Novel splittable N‐Tx/2N‐Rx transceiver phased array to optimize both signal‐to‐noise ratio and transmit efficiency at 9.4T. Issue 5 (27th November 2015) - Avdievich, Nikolai I.; Giapitzakis, Ioannis A.; Henning, Anke
Abstract : Purpose: The goal of this study was to optimize signal‐to‐noise ratio (SNR) and parallel receive (Rx) performance of ultrahigh field (UHF) (≥7T) transceiver arrays without compromising their transmit (Tx) efficiency. UHF transceiver head phased arrays with a tight fit improve Tx efficiency in comparison with Tx‐only arrays, which are usually larger so that Rx‐only arrays can fit inside. However, having ≥16 elements inside a head transceiver array presents decoupling problems. Furthermore, the available number of Tx channels is limited. Methods: A prototype of a splittable transceiver phased array was constructed. The array consisted of four flat surface Tx loops positioned in two rows. Each loop could be split into two smaller overlapped Rx loops during reception. Results: Experimental data demonstrated that both SNR and parallel reception performance improved substantially by doubling the number of Rx elements from four to eight. Conclusion: As a proof of concept, we developed and constructed a novel splittable transceiver phased array that allows doubling of the number of Rx elements while keeping both Tx and Rx elements at the same distance from the subject. Both Tx and Rx performance can be optimized at the same time using this method. Magn Reson Med 76:1621–1628, 2016. © 2015 International Society for Magnetic Resonance in Medicine